EKSEXPERIMENTAL DYNAMICS OF QUANTITATIVE CHANGES OF SOME MACROELEMENTS IN THE BLOOD OF KARAKUL LAMBS WITH HELMINTHIASIS - Khudjanova Muattar Absalomovna; Kodirova Sarvinoz Hakimovna (Web of Journals Publishing, 2024)
This article studies the effects and consequences of marshallagiosis, nematodirosis, and habertiosis helminthiases on the dynamics of quantitative changes of some macroelements (K, Na, Ca) in the blood composition of Karakul lambs.
Keywords: Karakul lambs, helminthiasis, preimaginal, postimaginal period, marshallagiosis, nematodirosis, habertiosis, macroelementiosis.